Efficient and Regioselectivity‐Tunable Metal‐Free Polycycloaddition of Activated Azide and Alkynes. Issue 4 (3rd January 2017) - Wu, Yongwei; He, Benzhao; Wang, Jia; Hu, Rongrong; Zhao, Zujin; Huang, Fei; Qin, Anjun; Tang, Ben Zhong
Abstract : An efficient and regioselectivity‐tunable metal‐free polymerization of activated azide and alkynes is established. Soluble polytriazoles with high molecular weights (up to 166 000) are obtained in excellent yields (up to 93%) under mild reaction conditions in air. Abstract : The transition‐metal catalyzed and metal‐free click polymerizations have been developed as powerful tools for the construction of functional polymers with linear and hyperbranched structures. The latter provides a thorough solution for the completely removing metallic residues from the products encountered in the former. Compared to the activated alkyne–azide metal‐free click polymerization, the activated azide–alkyne one is rarely studied. In this Communication, a perfluorophenyl‐activated azide of hexane‐1, 6‐diyl‐bis(4‐azido‐2, 3, 5, 6‐tetrafluorobenzoate) is rationally designed and facilely prepared. Through systematical optimization of the reaction conditions, an efficient metal‐free perfluorophenylazide–alkyne polycycloaddition is established, and polytriazoles with high molecular weights (up to 166 000) and excellent solubility are obtained in excellent yields (up to 93%) under mild reaction conditions. Interestingly, the regioselectivity of the reaction could be fine‐tuned by the solvents and diyne monomers. Therefore, this work provides not only a powerful tool for the preparation of functional polytriazoles, but also an attractive method for fine‐tuning their regioregularity.